Design of an Automatic Trash Can Based on Ultrasonic Sensors and Arduino at LP3I Medan Polytechnic - Tembusai, Zoelkarnain Rinanda; Santoso, Ahmad Imam; Butarbutar, Firma Deni (PT. Technology Laboratories Indonesia (TechnoLabs), 2026)
This study aims to design, develop, and test a prototype of an automatic trash bin based on HC-SR04 ultrasonic sensors and Arduino Uno R3 microcontrollers to improve cleanliness, efficiency, and awareness of waste management at the LP3I Polytechnic in Medan. This system is designed to detect the presence of users at a distance of less than 30 cm using an ultrasonic sensor, which then triggers the SG90 servo motor to automatically open the trash can lid and display information on capacity status and full warnings via a 16x2 LCD screen. After a 2-second delay, the lid will close again to prevent the spread of odors and maintain environmental hygiene. The prototype was developed through a research approach that included direct observation in the campus area, literature studies from reliable sources, and system design with hardware and software integration. Testing was conducted at strategic locations such as rest areas and campus corridors for 10 days, involving 100 trials with 10 daily tests per location. The test results showed a system effectiveness rate of 92%.